On Paracomplete Versions of Jaśkowski’s Discussive Logic - Mruczek-Nasieniewska, Krystyna; Petrukhin, Yaroslav; Shangin, Vasily (Bulletin of the Section of Logic, 2024)
Jaśkowski's discussive (discursive) logic D2 is historically one of the first paraconsistent logics, i.e., logics which 'tolerate' contradictions. Following Jaśkowski's idea to define his discussive logic by means of the modal logic S5 via special translation functions between discussive and modal languages, and supporting at the same time the tradition of paracomplete logics being the counterpart of paraconsistent ones, we present a paracomplete discussive logic D2p.